2005
DOI: 10.1007/s00442-005-0321-z
|View full text |Cite
|
Sign up to set email alerts
|

Using behavioural and state variables to identify proximate causes of population change in a seabird

Abstract: Changes in animal population size are driven by the interactions between intrinsic processes and extrinsic forces, and identifying the proximate mechanisms behind population change remains a fundamental question in ecology. Here we report on how measuring behavioural and state proxies of food availability among populations experiencing different growth rates can be used to rapidly identify proximate drivers of population trends. In recent decades, the Cape gannet Morus capensis has shown a major distributional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 47 publications
4
73
0
Order By: Relevance
“…As in most population studies [e.g. Lewis et al 2006] we observe the number of breeding birds at the peak of the breeding season. Using census data from 20 years , including the critical moment of the eastward shift in prey (late 1990s), we investigated the regional trends …”
Section: Introduction Seabirds and Their Environmentsupporting
confidence: 51%
“…As in most population studies [e.g. Lewis et al 2006] we observe the number of breeding birds at the peak of the breeding season. Using census data from 20 years , including the critical moment of the eastward shift in prey (late 1990s), we investigated the regional trends …”
Section: Introduction Seabirds and Their Environmentsupporting
confidence: 51%
“…6B) and was estimated at 5.86 kJ g −1 in the SB in the more recent period, whereas it was slightly less than 5 kJ g −1 in the NB (between 21% and 24% less than in the other studies). The Cape Gannet is probably the most specialized predator considered here, consistently deriving the largest portion of its diet from pelagic fishes (Berruti et al 1993), but also able to scavenge offal behind vessels fishing for hake (Lewis et al 2006, Pichegru et al 2010. Of the predator species discussed here, the Cape Gannet also has the largest potential feeding range.…”
Section: Trophic Interactions Between Predators and Their Preymentioning
confidence: 89%
“…As a result, although its food in the SB is entirely dominated by anchovies and sardines when they are available, in the NB, the sardine that dominated gannet diet in the 1950s has not been replaced by the low-energy bearded goby, which on average contributed <4% to the diet. Instead, gannets in the NB make longer feeding trips (Lewis et al 2006) and derive a higher percentage of their diet from trawler offal. Recently, Cape Gannets off South Africa's west coast have also turned to feeding on lower-energy discards from the hake fishery after the eastward shift in relative distribution of sardines and anchovies and have not been able to sustain breeding at the levels they achieved when more anchovies and sardines were available (Pichegru et al 2007).…”
Section: Trophic Interactions Between Predators and Their Preymentioning
confidence: 99%
“…These field techniques have been used on several occasions for cape gannets Morus capensis and in African penguins Spheniscus demersus , Lewis et al 2006, Pedersen et al 2006 with no measurable impact on the behaviour and the wellbeing of the animals. We nonetheless compared foraging trip durations of birds equipped with data loggers with those of non-equipped control birds.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been suggested that in long-lived species such as seabirds, foraging parameters recorded during the breeding season could be used to better understand the status of populations, based on the premise that foraging performance influences reproductive success, and ultimately recruitment (Lewis et al 2006). This approach is appealing from a management perspective, as studies of foraging behaviour can be performed within a much shorter timeframe than population studies, and results from the former can be quickly used as a base for management strategies.…”
Section: Introductionmentioning
confidence: 99%